Reverend Troy Perry, speaking on gay liberation - Cal Poly Gay Students' Union:::::::::
A flier for a joint meeting with the Cal Poly Gay Students' Union, in cooperation with Metropolitan Community Church SLO and Reverend Troy Perry - Speaking on Gay Liberation. The event was held at Chumash Auditorium, with free admission and open to the public.